Evaluating the effect of routing protocol, packet size and DSSS rate on network performance indicators in Manet's - Hakak, Saqib Iqbal (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Mobile Adhoc Network (MANET) is mostly used for emergency purposes as it requires neither infrastructure nor any centralized support. There are many issues in implementing MANETs. One of the key issues is dynamic nature of nodes that makes routing a difficult task. Many studies have focused on comparing routing protocols under varying network conditions. Following these studies, a question emerges, how much effect, quantified in percentage, routing protocols have on MANETs along with other factors that relate. Knowing the effect of packet size, direct sequence spread spectrum (DSSS rate) for example, helps network researchers and engineers in deploying IEEE 802.11b based MANET more efficiently. For this purpose, simulation has been performed under varying constant bit rate (CBR) data traffic load. Results have been evaluated using factorial design technique in order to quantify each parameter's contribution to the overall performance of the network. It shows that packet size of 256 and 512 bytes together has effect of 38% on average end to end delay and 42% on average jitter. On the other hand, routing mechanism influences the average delay and average jitter by 37% and 28% respectively. However, DSSS has an impact of 68.5% on overall throughput.